Criando meninos e meninas: investigação com famílias de um bairro de classe popular - Célia Regina Rangel Nascimento; Zeidi Araujo Trindade (Arquivos Brasileiros de Psicologia, 2010)
The aim of this study was to explore the educational practices for girls and boys in the family and to recognize the social representation of gender that guides these practices. The study had the participation of mothers, fathers and teenagers of both sexes of 44 families of a low income neighborhood. The data was collected through semi-structured interviews and analyzed using content analysis. Differences in the educational practices with sons and daughters identified by participants were grouped into the following thematic categories: Boys are more difficult, Girls are more difficult, Different concerns, Ways of talking, There is no difference, The house and the street. The participants revealed differences in the education of girls and boys and the results show the prevalence of the traditional social representation of gender that guides the practices with girls and boys in the families.